Wychowanie do mądrości – dydaktyczna perswazja w Jk 3,13-18 - Muszytowska, Dorota (Verbum Vitae, 2012)
The Letter of James is a didactic piece of writing. Its genre of parenetic letter or protreptic discourse and abundant usage of diatribe indicate that the author wants to show his readers the proper attitude to Christian life. James’ appeal is based on double-track argumentation: what is good and profitable vs. what is bad and unprofitable. Into this reasoning is inserted the argumentation of Jas 3,13-18, focused on appealing to Christian fellows to live their lives wisely. James distinguishes between worldly wisdom and God’s wisdom, and urges Christians to live according to the latter because it bears good fruits in the life of the community, such as justice, peace, concord, truth, gentleness. On the other hand, earthly wisdom, which he calls demonic, results in opposing negative values that can be noticed in social life. These are attitudes like quarrel, discord, envy, boastfulness, negation of truth. The conclusion that has to be deduced by the reader is evident – only the life guided by God’s wisdom is worth living.